DSM-5 and Mental Disorders in Older Individuals: An Overview. Issue 5 (September 2015) - Sachdev, Perminder S.; Mohan, Adith; Taylor, Lauren; Jeste, Dilip V.
Abstract : Learning Objectives: After participating in this activity, learners should be better able to: Assess the changes in DSM-5 relative to earlier versions. Evaluate the implications of the DSM-5 for practicing geriatric psychiatrists. Abstract: About every 20 years, the American Psychiatric Association revises its official classification of mental disorders. The fifth revision of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) was published in 2013, prompting considerable commentary, debate, and criticism. This article briefly describes the process leading up to DSM-5 and the main changes from the previous version (DSM-IV) that would be of interest to a geriatric psychiatrist. The changes in the areas of schizophrenia, bipolar disorder, depressive disorders, and anxiety disorders have been many, but the majority of them are minor and unlikely to have major treatment implications. The classification of neurocognitive disorders, however, has seen a major revision and elaboration in comparison to DSM-IV; of special note is the introduction of "mild and major neurocognitive disorders, " the latter equated with dementia. A common language has also been introduced for the criteria for the various etiological subtypes of neurocognitive disorders. All physicians treating patients with neurocognitive disorders should familiarize themselves with these criteria. Their use in research has the potential to harmonize the field.